Pendidikan Kesehatan Menggunakan Media Leaflet Menurunkan Kecemasan Pada Pasien Pre Anestesi Dengan Teknik Spinal Anestesi Di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Puji Rizky Affandi; Harmilah Harmilah; Budhy Ermawan (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Spinal anesthesia makes the patient remain conscious. 99% of people who will undergo anesthesia or surgery will experience pre anesthesia and surgery anxiety. Anxiety emerges because of several reasons, one of which is less information. By giving education through leaflet media, pateients are supposed to be more prepared to undergo the anesthesia process and get optimum results. The purpose of this research is to know the influence of health education by using leaflet media towards anxiety in pre anestesia patients with spinal anesthesia technique. This research method is using experimental quasi with two groups of intervention (leaflet) and control (visit only). The results of the research showed that pre-test anxiety in the intervention group was dominated by severe anxiety as many as 31 responden (86.11%), Medium anxiety was only one respondent (2.75%) and panic anxiety were 4 responden (11.11%), while the results of post-test in the intervention group experienced the decrease of anxiety on mild anxiety, namely 22 respondents (61.11%), Medium anxiety were 14 respondens (38.89%). From Mann Whitney statistical test with computer programs, it is obtained the output value of Asymp Sig. (2-tailed): 0,001 means that there is an influence on the use of leaflet media towards the decrease of anxiety in patients with spinal anesthesia in Prof. dr. Margono Soekarjo Hospital, Purwokerto.